Experiência de formação em residência multiprofissional como dispositivo de ampliação da clínica num hospital universitário - Oliveira, Deise Fernanda Peixoto (2014)
Some production devices of care and health, especially the expanded clinic, taking as reference a training experience on Multiprofessional Residency in Healthcare at the University Hospital of the Federal University of Sergipe, territory which I dwelt intensely for 2 years. To do so, it was grounded in the notion of care as encounter, openness attitude, based on the establishment of bonding, teamwork and integrality and transversality. The care involves different kinds of technologies and different ways of operating them. Health, in turn, is understood as a state in which the subject is able to set standards, of creating ways of living with news conditions. The research draws on cartographic method, whose challenge is to develop monitoring practices of inventive processes and production of subjectivities and the objective, map the network of forces that is connected to the object or researched phenomenon. , showing his permanent movement In the process of housing territory there is a affective responsiveness that involves no distinction between subject and object, researcher and field of research, theory and practice. It stands out from the experience of multiprofessional residency, effectiveness devices of the expanded clinic, analyzing how that produced transformations and ruptures. The clinic is understood as the meeting of subjectivities, experimentation, production that takes place in between, in and from the relationship, as practice of inclusion of the subject and its context beyond the illness. From an institutionalist perspective states that the training experience functioned as an analyzer device of the effectiveness practices of clinic in the hospital. Training not perceived as a knowledge transmission, but as "attitude" transdisciplinary, with power to produce openings to new sensibilities. The proposed training in multiprofessional residency provides openness to other viewpoints and ways of doing, expanding the possibilities of seeing the user and the production of health and care and contributes to the breakdown of specialisms and fragmentation of knowledge. Throughout the text are brought illustrative situations of concepts and themes discussed.